2014
DOI: 10.2478/plua-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition and Sensory Properties of Ciders Produced from Latvian Apples

Abstract: Polyphenol compounds are very important components of cider -they are responsible for the colour and the bitterness and astringency balance of cider. The polyphenolic profile of apples and apple drinks is influenced by several factors: apple variety, climate, maturity, and technological processes applied. This research paper concerns the influence of apple variety on the phenolic compounds and sensory properties of cider. Fermentation of 12 varieties of apple juice with Saccharomyces cerevisiae yeast '71B-1122… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
(18 reference statements)
2
17
0
Order By: Relevance
“…Oxygenation also increases the number of yeast cells, which can lead to an increase in the concentration of byproducts of the fermentation process, such as organic acids. The main secondary end product of alcohol fermentation is succinic acid, but low concentrations of pyruvic, malic, fumaric, oxaloacetic, citric, α-ketoglutaric, glutamic, propionic, and lactic acids are also present [22].…”
Section: The Effect Of Oxygenation On Oenological Parameters Of Cidersmentioning
confidence: 99%
“…Oxygenation also increases the number of yeast cells, which can lead to an increase in the concentration of byproducts of the fermentation process, such as organic acids. The main secondary end product of alcohol fermentation is succinic acid, but low concentrations of pyruvic, malic, fumaric, oxaloacetic, citric, α-ketoglutaric, glutamic, propionic, and lactic acids are also present [22].…”
Section: The Effect Of Oxygenation On Oenological Parameters Of Cidersmentioning
confidence: 99%
“…We have previously reported that ESNs are highly sensitive to glutamate excitotoxicity, with a median cytotoxic concentration of 0.44 mM glutamate (Gut et al, 2013). Based on published values, cell culture media supplemented with 1% milk or non-alcoholic cider contain 0.68 mM or 2.73 mM free glutamate, respectively (Giacometti, 1979;Riekstina-Dolge et al, 2014;Ventura et al, 2012). To test whether free glutamate was responsible for the acute loss of cell viability, the irreversible NMDAR antagonist MK-801 (10 mM) was administered to ESNs immediately prior to addition of each CM.…”
Section: Detection Of Bont/a Activity In Clinically Important Complexmentioning
confidence: 99%
“…Total phenolic compounds in liqueurs made from red fruits [17], wine [18][19][20][21], worts and beer [13,22,23], traditional fermented sorghum beers "dolo" [16], alcoholic beverages made from purple rice [24], ciders [25] and spirit drinks [26]; anthocyanins in liqueurs made from red fruits [17], dolo [16] and wine [21]; total flavonoids in wines [21]; and antioxidants capacity in wine [12,18,20,21], beer [23], liqueurs made from red fruit [17], alcoholic beverages made from purple rice [24] were determined.…”
Section: Introductionmentioning
confidence: 99%